Development Of Educational Interactive Game Media Based On Child-Friendly Learning In Mathematic Content To Improve Critical Thinking Understanding - Joko Sulianto; Achmad Buchori; Mei Riska Dwi Ariyanti (Proceeding International Conference on Digital Education and Social Science, 2025)
This research and development (R&D) aimed to test the feasibility (validity and practicality) and effectiveness of the Child-Friendly Learning-based Interactive Game Educational Media in improving fifth-grade elementary school students' understanding of mathematic The main problem identified was the lack of interactive use of conventional media, resulting in passive, unenthusiastic students, and difficulties in understanding the mathematic material. The development model used was ADDIE (Analysis, Design, Development, Implementation, Evaluation), and the study was conducted at Sambiroto Elementary School and Mojosari 2 Elementary School. The results showed that the EDUMIG media had excellent validity (Media Experts 94%, Material Experts 91.5%) and very high practicality (Teachers 97.3%, Students 100%). This media proved significantly effective, as evidenced by the T-Test results of 0.000 (<0.05), indicating a significant difference in the average scores between the two classes. The increased effectiveness was reinforced by the experimental class' N-Gain value of 0.659 (moderate category), significantly higher than the control class's (0.257, low category). Thus, Educational Interactive Game Media has successfully become a valid, practical, and effective innovative solution for increasing the motivation, engagement, and conceptual understanding of mathematic students.